A composite approach to Air Force planning - Davis, Paul K., 1943-; Khalilzad, Zalmay; Rand eBooks (Santa Monica, CA : RAND, 1996)
After the 1996 Presidential election, the Department of Defense (DoD) will probably conduct a major review of national military strategy and the current basis of force planning, the Bottom-Up Review. In preparation for this review, what issues should the Air Force consider, what planning methods should be brought to bear, and when? The authors address these questions and note that there is no single best planning method. Different methods focus on and deal with different generic planning activities, and no method stands alone or constitutes a complete methodology. If undertaken by creative minds, most of the techniques discussed here will do a good job for the Air Force (and for the DoD more generally). But it is particularly important to allow and encourage participants to break the shackles of conventional wisdom--not only about current realities, but about what the nature of the future will be, about what "good" strategic planners are "supposed" to assume about the future, and what types and levels of forces are allegedly "required."
"Project Air Force."
Includes bibliographical references (p. 47-50).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Management; Military planning -- United States; Electronic books